G2-block after irradiation of cells with different p53 status - Zölzer, Friedo; Jagetia, Ganesh; Streffer, Christian (Strahlentherapie und Onkologie, 2014)
BACKGROUND: Although it is clear that functional p53 is not required for radiation-induced G2 block, certain experimental findings suggest a role for p53 in this context. For instance, as we also confirm here, the maximum accumulation in the G2 compartment after X-ray exposure occurs much later in p53 mutants than in wild types. It remains to be seen, however, whether this difference is due to a longer block in the G2 phase itself. MATERIAL AND METHODS: We observed the movement of BrdU-labeled cells through G2 and M into G1. From an analysis of the fraction of labeled cells that entered the second posttreatment cell cycle, we were able to determine the absolute duration of the G2 and M phases in unirradiated and irradiated cells. RESULTS: Our experiments with four cell lines, two melanomas and two squamous carcinomas, showed that the radiation-induced delay of transition through the G2 and M phases did not correlate with p53 status. CONCLUSION: We conclude that looking at the accumulation of cells in the G2 compartment alone is misleading when differences in the G2 block are investigated and that the G2 block itself is indeed independent of functional p53.
Keywords: Tumor Suppressor Protein p53; G2 Phase Cell Cycle Checkpoints; Neoplasms, Experimental; lidé; Cell Survival; Radiation Dosage; viabilita buněk; dávka záření; Cell Line, Tumor; kontrolní body fáze G2 buněčného cyklu; vztah dávky záření a odpovědi; nádorové buněčné linie; nádorový supresorový protein p53; experimentální nádory; Dose-Response Relationship, Radiation; Humans